Effects of Clostridium perfringens iota toxin in the small intestine of mice - Redondo, Leandro Martin (2017)
Iota toxin is a binary toxin solely produced by Clostridium perfringens type E strains, and is structurally related to CDT from C. difficile and CST from C. spiroforme. As type E causes hemorrhagic enteritis in cattle, it is usually assumed that associated diseases are mediated by iota toxin, although evidence in this regar has not been provided. In the present report, iota toxin intestinal effects were evaluated in vivo using a mouse model. Histological damage was observed in ileal loops treated with purified iota toxin after 4 h of incubation. Luminal iota toxin induced fluid accumulation in the small intestine in a dose dependent manner, as determined by the enteropooling and the intestinal loop assays. None of these changes were observed in the large intestine. These results suggest that C. perfringens iota toxin alters intestinal permeability, predominantly by inducing necrosis and degenerative changes in the mucosal epithelium of the small intestine, as well as changes in intestinal motility. The obtained results suggest a central role for iota toxin in the pathogenesis of C. perfringens type E hemorrhagic enteritis, and contribute to remark the importance of clostridial binary toxins in digestive diseases.